Techno-productive experiences for climate action in Argentina: Insights from renewable energy projects - Canafoglia, Eliana Celeste (2024)
The main purpose of this research is to analyze techno-productive experiences within the framework of renewable energy projects based on the use and exploitation of solar energy in a region defined by favorable bioclimatic conditions. Following a primarily qualitative method, the research has been based on four case studies of working groups and their experiences. Stakeholders from diverse origin and background, interested in developing their technologies (processes, inputs, components, equipment) for the use of solar energy have managed to enhance the links among such developments, the productive sector and the communities in the territorial area where they carry out their activities. As a possible path of sociotechnical transition, these specific processes materialize energy transition with the progressive change of production and consumption patterns in favor of climate action.